PEMASARAN USAHATANI JERUK SIAM KINTAMANI - I Made Ariana Darma Satriya Banjar; Putu Fajar Kartika Lestari; Ni Putu Sukanteri; Komang Dean Ananda (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Langgahan Kauh Village, is one of the villages that still has agriculture, namely Citrus nobilis. This study aims to determine the marketing channels used by Citrus nobilis farmers in marketing Citrus nobilis in Langgahan Kauh Village, Kintamani District, Bangli Regency and to find out what the costs, marketing margins, and profits of Citrus nobilis are in Langgahan Kauh Village, Kintamani District, Bangli Regency. This research was conducted from October to December 2021. Respondents were determined using the incidental method with a sample of 33 Citrus nobilis farmers. The data analysis method used is descriptive analysis, marketing margin analysis, profit margin analysis, stock analysis, efficiency analysis and income analysis. The results of this study indicate that the existing marketing channels in Langgahan Village, Kintamani District, Bangli Regency are very efficient in terms of marketing channel I where the efficiency is 3.3%. while for the marketing costs obtained in channel I of Rp. 200/kg while channel III Rp. 1,470/kg. While the marketing margin obtained in channel I is Rp. 0/kg. Meanwhile, what is obtained on channel III is 8,500. The profit margin in marketing channel I is 0 rupiah, while the profit margin in channel III is 6,730. And the production of Citrus nobilis per season is an average of 21,061kg. with an average area of ​​58.5 hectares. The production value or income of Citrus nobilis farming is Rp. 105,305,000. Citrus nobilis farming income is Rp. 74,737,414 per production season with an R/C ratio of 3.44